2021
DOI: 10.3389/fpsyg.2021.585547
|View full text |Cite
|
Sign up to set email alerts
|

Game Transfer Phenomena and Problematic Interactive Media Use: Dispositional and Media Habit Factors

Abstract: The study of the effects of interactive media has mainly focused on dysregulated behaviors, the conceptualization of which is supported by the paradigms of addiction. Research into Game Transfer Phenomena (GTP) examines the interplay between video game features, events while playing, and the manipulation of hardware, which can lead to sensory-perceptual and cognitive intrusions (e.g., hallucinations and recurrent thoughts) and self-agency transient changes (e.g., automatic behaviors) related to video games. GT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Increases in playing time have been found to be associated with GTP ( Ortiz de Gortari et al, 2015 , 2016 ; Dindar and Ortiz de Gortari, 2017 ), but discrepancies have also been found between hours played a week and playing session length. Some studies have even found that the hours played per day were not associated with GTP ( Ortiz de Gortari and Gackenbach, 2021 ). The validation of the original GTPS used session length for criterion-related validity ( Ortiz de Gortari et al, 2015 ; Dindar and Ortiz de Gortari, 2017 ).…”
Section: Factor Analysis Of the Game Transfer Phenomenamentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in playing time have been found to be associated with GTP ( Ortiz de Gortari et al, 2015 , 2016 ; Dindar and Ortiz de Gortari, 2017 ), but discrepancies have also been found between hours played a week and playing session length. Some studies have even found that the hours played per day were not associated with GTP ( Ortiz de Gortari and Gackenbach, 2021 ). The validation of the original GTPS used session length for criterion-related validity ( Ortiz de Gortari et al, 2015 ; Dindar and Ortiz de Gortari, 2017 ).…”
Section: Factor Analysis Of the Game Transfer Phenomenamentioning
confidence: 99%
“…It is fundamental to understand the degree of which the assessment of GTP can support the identification of factors that contribute to the maintenance of gaming disorder (GD) symptoms and relapse. Various studies have shown associations between GD and GTP ( Ortiz de Gortari et al, 2016 ; Jones-Rincon et al, 2021 ; Ortiz de Gortari and Gackenbach, 2021 ; Llamas-Alonso et al, 2022 ) and GTP have emerged as a mediator of factors for gaming disorder (e.g., gaming features and emotion regulation) ( Cudo and Zabielska-Mendyk, 2022 ). For instances, the assessment of GTP in clinical cases of GD has shown to be beneficial for understanding the evolution of patient symptomatology and establishing differential diagnoses of psychosis ( Ortiz de Gortari and Basche, 2021 , 2022 ).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Various underlying psychopathological factors have been found to be associated with GTP (e.g., schizotypal personality, neuroticism, depression, anxiety, ADHD, and problematic gaming) [17] , [20] , [28] , [33] , but, in most cases, players who reported experiencing GTP have had no clinical diagnosis [27] ; Ortiz de Gortari & Griffiths, 2016a; [33] . However, research has found that those who experience GTP more frequently and in various forms are significantly more likely to have used drugs, suffer from a mental disorder, and experience distress or dysfunction due to their GTP experiences [32] .…”
Section: Introductionmentioning
confidence: 99%
“…Further, sense of embodiment likely plays a role in the Proteus effect, of the phenomenon that an avatar's characteristics influence the user's subsequent behaviors (Yee and Bailenson, 2007 , 2009 ; Ratan et al, 2020 ). Thus, while the individual's real-life background and knowledge, either directly and/or indirectly, predicate the avatar's formation, the avatar can also influence the user's conduct outside of the virtual world in subtle, although significant ways (e.g., distorted perceptions, cognitions, and even non-deliberate actions Ortiz de Gortari and Gackenbach, 2021 ; Navarro et al, 2022 ).…”
mentioning
confidence: 99%